Towards a Sustainable Well-being Model: Integrating the Joyful School Movement into Primary School Governance - Hasanah, Usrotun; Nyoman, Ngurah Ayu; Prayito, Muhammad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyse the implementation of the Joyful School Movements (GSM) in strengthening student well-being through school management processes. A qualitative case study was conducted in an elementary school, using in-depth interviews, classroom observations, and document analysis. Data analysis was conducted using an interactive model that included data reduction, data presentation, and the drawing and verification of conclusions. The results show that GSM is implemented through four interrelated stages: shared understanding, participatory planning, transformative implementation, and reflective evaluation. These stages foster a sense of psychological safety, increase student engagement, and promote a positive, collaborative school climate. This study proposes an integrative school well-being management model that links pedagogical practices with school governance structures to support sustainable educational transformation and prioritise student well-being. This study provides implications that implementing GSM through integrated stages can be an effective strategy in building school well-being. Educational institutions need to develop participatory and reflective practices that support psychological safety, increase student engagement, and strengthen a positive, collaborative, and sustainable school climate.